(untitled) (gjstudies, 2018)
This research investigates the persistent and widening misalignment between contemporary accounting education curricula and the evolving demands of professionalpractice, proposing a novel, dynamic alignment framework rooted in systems theoryand anticipatory competency modeling. Traditional approaches to curriculum design,often reactive and lagging, are critiqued for their inability to keep pace with the rapidtransformation of the accounting profession driven by regulatory shifts, technologicaldisruption, and expanding stakeholder expectations. The study formulates a centralresearch question: How can accounting education systems be structurally redesigned toachieve proactive, rather than reactive, alignment with professional practice demands?To address this, we introduce the Integrated Dynamic Alignment Model (IDAM), amethodology that departs from conventional gap analysis by incorporating continuousenvironmental scanning, stakeholder sentiment analysis via natural language processing of professional discourse, and a feedback-driven curriculum adaptation engine. Themodel conceptualizes the curriculum not as a static document but as a living systemwith embedded sensors and actuators. Our empirical investigation applies IDAM to analyze curriculum documents from twenty-five accredited accounting programs againsta real-time corpus of job advertisements, professional body publications, and regulatory announcements from 2000 to 2004. The results reveal a significant and systemiclatency, with educational institutions taking an average of 18 to 36 months to integrateemergent practice demands, such as ethics in financial engineering, forensic data analytics, and sustainability assurance, into core syllabi. Furthermore, the study uncoversa critical ’competency attenuation’ effect, where even upon integration, the pedagogical treatment of new competencies often lacks the depth and contextual complexityrequired in practice. The paper concludes by arguing that the future relevance of accounting education hinges on adopting such systemic, anticipatory models, shifting theparadigm from curriculum maintenance to curriculum evolution. This represents anoriginal contribution by framing the alignment problem through a cybernetic lens andoffering a tangible, operational model for continuous curricular transformation.